Elite mountain bike enduro competition: a study of rider hand-arm vibration exposure - Kirkwood, L. A.; Taylor, M. D.; Ingram, L. A.; Malone, E.; Florida-James, G. D. (Journal of Science and Cycling, 2019)
Limited information is currently available regarding the hand-arm vibration (HAV) exposure for professional off-road cyclists. Previous reports have suggested that commuting and recreational cyclists are at risk of exceeding exposure limit values (ELV) in a single ride and, therefore, further investigation of HAV exposure in competitive mountain biking is warranted. Partial and total eight hour exposure data (Ai(8), A(8), ms-2) are presented for a national level mountain bike race. Assessment of hand-arm vibration meets the requirements of BS EN ISO 5349-1:2001 (BSI 2001) whereby recording frequency was 3.2 kHz and frequency weighting filters were applied (Wh). The data presented shows that HAV exposure during one day of competitive enduro mountain bike racing exceeds ELV and is greater than the HAV exposure observed in recreational cycling. This suggests that further work is required to determine the exposure associated with changes in equipment, technique and international racing events in professional athletes.